Synthesis of 2,4-Diarylquinoline Derivatives via Chloranil-Promoted Oxidative Annulation and One-Pot Reaction - Cheng, Dongping; Yan, Xianhang; Shen, Jing; Pu, Yueqi; Xu, Xiaoliang; Yan, Jizhong (Synthesis, 2020)
An oxidative annulation for the synthesis of 2,4-diarylquinolines from o-allylanilines is disclosed that uses recyclable reagent Chloranil as the oxidant. The corresponding products are obtained in moderate to excellent yields. Furthermore, a one-pot access to 2,4-diarylquinolines from easily available anilines and 1,3-diarylpropenes is described as a highly atom-efficient protocol that involves oxidative coupling, rearrangement, and oxidative annulation.
Keywords: oxidative annulation; one-pot reaction; chloranil; 2,4-diarylqunoline